Michael addition of N-unprotected 2-oxindoles to nitrostyrene catalyzed by bifunctional tertiary amines: Crucial role of dispersion interactions - Reiter, Christoph; Lopez-Molina, Sonia; Schmid, Bernhard; Neiß, Christian; Görling, Andreas; Tsogoeva, Svetlana (ChemCatChem, 2014)
Bifunctional thiourea- or sulfonamide-derived tertiary amines catalyze the enantioselective nitro-Michael addition of N-unprotected 3-substituted 2-oxindoles to nitrostyrene in up to 99 % yields, 94:6 er, and 87:13 dr. Overcoming the necessity to introduce and remove activating or protecting groups at the nitrogen moiety leads to a reduction of energy use, costs, and waste. Transition-state geometries for the formation of all possible stereoisomers in the nitro-Michael addition of N-unprotected 3-substituted 2-oxindole to nitrostyrene catalyzed by Takemoto's tertiary amine-thiourea are calculated. It is shown that the relative positions and binding patterns of the reactants and the catalyst molecule are largely determined by van der Waals interactions. The importance of being dispersed: Bifunctional thiourea- or sulfonamide-derived tertiary amines such as Takemoto's catalyst catalyze the enantioselective nitro-Michael addition of N-unprotected 3-substituted 2-oxindoles to nitrostyrene in high yields and enantiomeric and diastereomeric ratios. DFT calculations including van der Waals corrections are performed for the stereoisomers. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: density functional calculations; enantioselectivity; Michael addition; noncovalent interactions; organocatalysis